Analisis Praktik Pembulatan Timbangan pada Jasa Franchise Simply Fresh Laundry dalam Perspektif Hukum Islam - Muhammad, Fattah Muharrik; Fitroh, Khairul; Faishal, Abdullah Jundi (Journal of Fiqh in Contemporary Financial Transactions, 2024)
This research was conducted to determine the practice of rounding scales for laundry services in the Simply Fresh Laundry Franchise and a review of sharia economic law regarding rounding of scales for laundry services in the Simply Fresh Laundry Franchise. The method used in this research is empirical Islamic legal research or field Islamic legal research, which involves collecting data directly on the research object. The observation results show that the practice of rounding the scales has been implemented in the Simply Fresh laundry service. Despite initial reservations from some customers, most supported it because it made transactions easier. The rounding of the scales at Simply Fresh Laundry is considered in accordance with 'Urf Sahih and 'Urf Amali because it follows community customs, does not violate religious teachings, and is consistently accepted. The legal view is in line with the rules of al adah muhakkamah fiqh, with the laundry informing customers of this practice, the majority of whom understand, so it is considered to be in accordance with the teachings of the Qur'an and Sunnah.